PERANCANGAN PASAR BARU MARABAHAN - Al-Arif, Abdurrahman; Mentayani, Ira (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
Marabahan City is the capital city of Barito Kuala which is also the center of government and economy, seen from the arrangement of the city between the government and the community's economic center located in the market. Marabahan City also gets the motto of the word Bahalap (beautiful) contrary to the existence of market arrangements and lacking facilities for the community where the source of the economy for most of the people of the Marabahan city are farmers and traders.For the arrangement of the city of Marabahan with the market design for the community with facilities and analysis based on the environmental situation of the city of Marabahan using a behavioral architectural approach with the Behavior setting method. Which combines two aspects, namely between the environment and people's behavior.The result of the design of the new Marabahan market is the existence of stalls for retail traders and the arrangement of stalls and shops and even the layout of the motorcycle parking lot which used to use the main road.